Food and feeding habits of the Indian catfish (Heteropneustes fossilis (Bloch)) from Tigris river at AI- Kadhimia region, north of Baghdad city - M.Da.uod, H. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
F0od  and  feeding habits  of  Hetropnezt.s!fes ]ossili/}:. (Bloch)  have been  investigated.  Monthly samples (twice a  m()nth}  were   taken during  the period  from  March  2000  to February  20.Ql , using small -meshed cast net. A total of l9J  ftsh were used to examine the stomachcontents.The analysis   of  stomach contents of H  fo.s-silis in  the- area  of study  revealed   that  fish  were  fed  on  the  bottom, mid Â·surface  and surface   food.   The  main   fb.od   of  the   fish   were  pbyt9planktons, moUuscs, ,chironomid  larvae and pupae and higher plants which mean that the- species under investigatiofl  prefer to be camivoro_us in the area of  study.  the study  of  variation  in feeding  intensity  of  H. fossilis , showed  that  the   highest   feeding  intensity   was  observed  during sununet  months   while   the  lowest   was  during   autumn   and   such variation  occurred  due  to the a:vailability of food  in the J1abitat, thechanges  in temperatureÂ·s and for  perhaps Â· due to the  feeding  habits of this species.